Pengaruh Intellectual Capital, Good Corporate Governance, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan - Elvia Kholida Fauziyati; Fauzan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the impact of Intellectual Capital, Good Corporate Governance, and Firm Size on Financial Performance of banking companies listed on the Indonesia Stock Exchange during the period of 2021-2022. The research uses a quantitative approach with data analysis conducted using SPSS for Windows 27. The population includes all banking companies listed on the IDX, with a sample selected using purposive sampling technique. The results of the simultaneous test show that all independent variables have a significant impact on financial performance, measured by Return On Asset (ROA) (significance value of 0.004). Partially, Intellectual Capital and Firm Size have a significant effect on financial performance, while Good Corporate Governance does not have a significant impact. This study has limitations in using only three factors and suggests adding more variables and extending the observation period in future research.